2015
DOI: 10.1039/c5nj00294j
|View full text |Cite
|
Sign up to set email alerts
|

Silver sputtering into a liquid matrix containing mercaptans: the systematic size control of silver nanoparticles in single nanometer-orders

Abstract: We herein propose a novel methodology to synthesize silver nano-particles with precisely controlled diameters in single nano-meter orders by sputtering into a liquid matrix (polyethylene glycol) containing mercaptans (11-mercaptoundecanoic acid) as an environmental friendly preparation without reductants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 26 publications
0
55
0
Order By: Relevance
“…Moreover, some groups have applied the results to various nonvolatile liquids such as functionalized ILs, 45,46 castor oil, 47 and low-molecular-weight polymers. [48][49][50][51][52] In this study, we limit our subject to Au nanoparticles (AuNPs) synthesized by the sputter deposition-technique in imidazolium-based ILs. In the first report on this method, Torimoto et al showed that the sizes of AuNPs are dependent on the type of IL.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some groups have applied the results to various nonvolatile liquids such as functionalized ILs, 45,46 castor oil, 47 and low-molecular-weight polymers. [48][49][50][51][52] In this study, we limit our subject to Au nanoparticles (AuNPs) synthesized by the sputter deposition-technique in imidazolium-based ILs. In the first report on this method, Torimoto et al showed that the sizes of AuNPs are dependent on the type of IL.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 This synthetic method takes advantage of the extremely low vapor pressure of liquid matrices so that the preparation of NPs can be carried out at low pressure or under high vacuum conditions. 11,12 This approach can be expanded to other combinations of liquid matrices and thiolate ligands, and will broaden the spectrum of NP chemistry using this sputtering technique. Ejected atoms and clusters coalesce into NPs in the gas phase or at the interface of the liquid matrix.…”
mentioning
confidence: 99%
“…Sample (a), which shows plasmon absorption in Fig. 11,12 This phenomenon is attributed to the quantum size effect, 18 in which a band gap of NPs depends on the number of atoms making up a particle. On the other hand, samples (b) and (c) fluoresced in the near IR region.…”
mentioning
confidence: 99%
“…First, metal NP synthesis using ionic liquids will be discussed, which includes the synthesis of single material NPs and the effect of sputtering conditions [19][20][21][22][23][24][25][26][27], various alloying strategies [15,23,24,28], and techniques for transferring synthesized NPs [29][30][31]. Subsequently, we discuss NP synthesis using low-volatile polymers, including the use of thiol compounds and transfer techniques [32][33][34][35][36][37][38][39]. Finally, potential applications of liquid medium sputtered NPs, such as their use as ORR electrocatalysts and Suzuki-Miyaura coupling reacScheme.…”
Section: Introductionmentioning
confidence: 99%
“…Ishida et al used a thiol stabilizer to enhance the stabilization ability of PEG. Ag was sputtered onto PEG containing 0, 5.2 × 10 , and 5.2 × 10 -1 M of 11-mercaptoundecanoic acid (MUA) using a current of 30 mA under Ar at a pressure of 2.0 Pa [37]. Altering the concentration of MUA in PEG afforded direct control of the size of resulting Ag NPs, with particles ranging from 2.2 to 7.4 nm in diameter (Fig.…”
Section: Introduction Of Thiol Functional Groupsmentioning
confidence: 99%